Investigations on the impact toughness of HSLA steel arc welded joints. (January 2016) - Pamnani, Rishi; Jayakumar, T.; Vasudevan, M.; Sakthivel, T.
Abstract: The impact toughness of HSLA steel weld joints fabricated by arc welding processes was studied. The influence of inclusions and microstructural characteristics of SMAW, SAW, FCAW and A-GTAW on the toughness of the weld metals were investigated. The inclusion size, area fraction and number density were analyzed using image analysis software. The area fraction and the number of inclusions per mm 2 indicated maximum inclusions in SAW followed by FCAW, A-GTAW and SMAW. It was observed that finer inclusion size and lower inclusion content can be related with higher impact toughness of the weld joints at room temperature. At sub-zero temperatures, the impact toughness of the weld metals of various arc welded joints was found to be influenced by the weld metal grain size, chemical composition of weld metal, acicular ferrite and inclusion content.